Reimagined MPFL Reconstruction: Retinacular Fixation of the Doubled Hamstring Graft at the Patella and Suture Anchor-Based Femoral Fixation - Muhammed Ehsan Nazeer; Sagar Goel; Muhammed Nazeer; Gowrishankar Sreenivasan; Mohsin Nazeer Muhammed; Suzaan Shajil (Advances in Orthopedics)
Background. Lateral patellar dislocation is frequently observed among teenagers and young adults. There is no consensus on the best type of graft or fixation strategy for the femur and patella, and complications such as iatrogenic patella fracture, tunnel malposition, and grafting failure are common. The objective of our research is to find out the functional outcome of a new method of medial patellofemoral ligament (MPFL) reconstruction, which involves two key components: (1) patellar fixation is accomplished by suturing the two limbs of the looped doubled hamstring graft in a divergent fashion to the retinaculum at the medial border of the upper half of patella and (2) the placement of a suture anchor tied to the graft at the isometric point on the medial femur condyle. Methods. This study is a retrospective assessment of patients who underwent MPFL reconstruction at our hospital between September 2018 and August 2020. Patients were monitored for at least 2 years after the initial procedure until August 2022. Results. A total of 29 patients were recruited for the study, with 22 being females and the average age being 30.38 years. During the postoperative period, none of the participants experienced instability, redislocation, patellar/femoral fractures, or abnormal distal femur growth. The Tegner–Lysholm knee score was good to excellent for 17 (58.6%) participants, fair for 10 (34.5%) participants, and poor for 2 (6.9%) participants. The Kujala anterior knee pain score was more than 80 for 19 (65.5%) participants. Conclusion. This research presents a significant achievement rate of the surgical procedure, accompanied by the mean Tegner–Lysholm knee score of 82.68 and the mean Kujala anterior knee pain score of 82.71. Notably, there were no complications observed in the postoperative period.